FIRST REPORT OF METACERCARIAE (DIGENEA) INFECTING ASTRONOTUS OCELLATUS (PERCIFORMES: CICHLIDAE) FROM THE AMAZON REGION, BRAZIL - Tavares-Dias, Marcos (2011)
This study aimed to report infection by metacercariae ofthe genera Posthodiplostomum Dubois, 1936 (Diplostomidae) and Herpetodiplostomum Dubois, 1936 (Proterodiplostomidae) in the gills of Oscar Astronotus ocellatus Agassiz, 1831 (Cichlidae) from Lake Pracuúba, in the municipality of Pracuúba, State of Amapá (eastern Amazonia), Brazil. Out of 202 A. ocellatus examined, 142 had gills infected by metacercariae of Herpetodiplostomum sp. (prevalence= 70.3%) and Posthodiplostomum sp. (prevalence= 59.4%). However, 97 hosts were infected by both metacercariae species (prevalence= 48.0%). A total of 1123 specimens of Herpetodiplostomum sp. and 463 specimens of Posthodiplostomum sp. were collected and the mean intensity of infection was 7.8 ± 11.6 and 3.9 ± 4.4, respectively. This is the first report of Digenea in A. ocellatus.